Harmonization of programmed death‐ligand 1 immunohistochemistry and mRNA expression scoring in metastatic melanoma: a multicentre analysis. Issue 7 (5th May 2022) - Darmon‐Novello, Marie; Adam, Julien; Lamant, Laurence; Battistella, Maxime; Ortonne, Nicolas; Balme, Brigitte; de la Fouchardière, A; Chaltiel, Leonor; Gerard, Emilie; Franchet, Camille; Vergier, Béatrice
Abstract : Aims: The aim of this multicentre study was to harmonize programmed death‐ligand 1 (PD‐L1) immunohistochemistry (IHC) and melanoma scoring. To provide a reference for PD‐L1 expression independently of the IHC protocol, PD‐L1 mRNA expression was compared with IHC. Methods and results: Standardized PD‐L1 assays (22C3, 28–8, SP142, SP263) and laboratory‐developed tests (QR1, 22C3) were evaluated on three IHC platforms with a training set (seven cases). mRNA expression was determined by RNAscope (CD274/PD‐L1 probe) and analysed with image analysis. PD‐L1 IHC findings were scored by seven blinded pathologists using the tumour proportion score (TPS), the combined positive score (CPS), and the MELscore. This method was validated by three blinded pathologists on 40 metastatic melanomas. Concordances among various antibody/platforms were high across antibodies [intraclass correlation coefficient (ICC) >0.80 for the CPS], except for SP142. Two levels of immunostaining intensity were observed: high (QR1 and SP263) and low (28–8, 22C3, and SP142). Reproducibilities across pathologists were higher for QR1 and SP263 (ICC ≥0.87 and ICC ≥0.85 for the TPS and the CPS, respectively). QR1, SP263 and 28–8 showed the highest concordance with mRNA expression. We developed a standardized method for PD‐L1 immunodetection and scoring, tested on 40 metastatic melanomas. Concordances among antibodies were excellent for all criteria, and concordances among pathologists were better for the MELscore than for other scores. Conclusion: Harmonization of PD‐L1 staining and scoring in melanomas with good concordance is achievable with the PD‐L1 IHC protocols applied to other cancers; this reproducible approach can simplify daily practice. Abstract :